The life and work of Martina Orožen: On the occasion of her 90th birthday, 12 October 2021 - Jesenšek, Marko (Slavia Centralis, 2021)
This paper presents the life of Martina Orožen, born on 12 October 1931 in Turje, honored professor of Historical Grammar and Dialectology of the Slovene Language at the Department of Slavic Languages and Literature, Faculty of Arts, University of Ljubljana – she spent her childhood in Turje, a family tragedy happened during the Second World War, she went to the grammar school in Celje, then she studied Slavic Studies in Ljubljana and got employed at the Faculty of Arts of the University of Ljubljana, then received further study training and held guest lectures in Warsaw, Krakow, Vienna, Graz and Klagenfurt.
Keywords: Martina Orožen; Turje; life and work; Slovene language; historical grammar